Dietary valine requirement of juvenile Nile tilapia, Oreochromis niloticus. (13th May 2017) - Xiao, W.; Li, D.Y.; Zhu, J.L.; Zou, Z.Y.; Yue, Y.R.; Yang, H.
Abstract: An 8‐week feeding trial was conducted to quantify the dietary valine requirement of cultured juvenile Nile tilapia, Oreochromis niloticus . Six isonitrogenous (280 g/kg crude protein) and isoenergetic (16.06 MJ/kg gross energy) diets with graded levels of valine (amounting to 4.1, 7.2, 9.9, 12.7, 15.6 and 18.8 g/kg of dry diet) were formulated. Each diet was randomly assigned to triplicate groups of 20 fish (6.48 ± 0.06 g). Results showed that the weight gain, specific growth rate, protein efficiency ratio and protein retention efficiency all increased with an increasing level of dietary valine up to 12.7 g/kg, but remained relatively constant for fish fed higher levels of dietary valine. In addition, the total protein concentration and aspirate aminotransferase activity in plasma, hepatic lysozyme and catalase activities were all significantly ( p  <   .05) improved by dietary valine supplementation. Based on the broken‐line regression analysis of weight gain and protein retention efficiency, the optimal dietary valine requirement for juvenile Nile tilapia occurred between a level of 11.5 g/kg of diet (equivalent to 41.1 g/kg of dietary protein) and 12.7 g/kg of diet (equivalent to 45.3 g/kg of dietary protein).